Career Preparation and Graduate Earnings: Evidence from Internships, Counseling, and Workshops in Islamic Economics and Business Education - Rizky Fatmawati; Nurul Hasanah Syah; Juliana Nasution; Fahmi Zulfandy (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
In today’s competitive labor market, many graduates, particularly those from Islamic business faculties, struggle to secure jobs that match their qualifications and ensure sustainable income. There is growing concern about the gap between educational preparation and post-graduation earnings, especially regarding the effectiveness of structured career preparation programs. This study aims to examine the influence of three key career preparation strategies: industrial internships, career counseling training, and career workshops on the earnings of graduates from Islamic business education programs. Using a quantitative approach, the study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze data collected from a sample of 347 students out of a total population of 2,617 from the Faculty of Islamic Economics and Business at Sheikh Abdul Halim Hasan Binjai Institute. The findings show that the three variables industrial internships, career counseling training, and career workshops, have a significant and positive impact on graduate income. Internships provide real-world experience that enhances employability, counseling supports informed career decision-making, and workshops strengthen soft skills relevant to the labor market. Career preparation programs play an essential role in improving the economic outcomes of Islamic business graduates. Higher education institutions should integrate practical activities, consultation, and skill enhancement to bridge the gap between academic learning and labor market demands. This study uniquely contributes to the literature by focusing on career preparation in the context of Islamic higher education, an area that remains largely under-researched. It offers empirical evidence of how structured interventions can increase graduate income and provides strategic insights for curriculum developers, policymakers, and educational institutions seeking to improve graduate employability through holistic preparation mechanisms.